Development of A Gyratory Bladed Grinding Machine for Ripe Plantain Processing - Aiki Habeebullahi Opeyemi; Buliaminu Kareem; Adeola Adeyemi James (International Journal of Industrial and Product Design Engineering, 2024)
The processing of ripe plantains faces significant challenges, including inefficient grinding and mortar pasting methods, inconsistent paste quality, and maintenance difficulties with existing equipment. This paper presents the development of a gyratory bladed grinding machine specifically for ripe plantain processing. SOLIDWORKS CAD software was applied to create the machine's CAD, or computer-aided design, model. The design analysis of the machine components was conducted, and appropriate materials were selected to accommodate the unique properties of ripe plantains. Performance evaluation of the machine was conducted and through the series of tests, the machine has an operational efficiency of 73.32% and can grind 100 plantains within an hour. This machine bridges the gap between small-scale farming and industrial food production, contributing to localised food processing and enhancing agricultural advancement.
Keywords: Ripe plantains; food production; grinding; gyratory bladed grinding machine